Differences in motor abilities between competitive and recreational karate practitioners at adolescent age - Grubješić Miloš; Stanković Ognjen (College of Sports and Health, Belgrade, 2020)
Motor skills as a characteristics involved in solving motor tasks are not equally developed in every individual, whether he or she is an athlete, recreational athlete or is not engaged in physical activity. The aim of this study was to determine the differences in motor skills of adolescents engaged in karate, but at different volume and intensity. The sample consisted of 30 karate practitioners aged 14 and 15, divided into two groups of 15 players. A battery of seven tests was used to assess their motor skills. In statistical data processing, descriptive statistical analysis and the Mann Whitney U test were applied to determine the difference between groups at the level of statistical significance p <0.05. Research has shown that competitive karate practitioners performed better in the tests of explosiveness, repetitive power, endurance, speed and agility. Statistically significant differences in these tests were expected as competitors dedicated more time to training strength, explosiveness and endurance. There were no statistically significant differences in the tests of flexibility and balance, which was partially expected because of the nature of the sport the respondents are engaged in.